Human MAIT‐cell responses to Escherichia coli: activation, cytokine production, proliferation, and cytotoxicity. Issue 1 (31st March 2016) - Dias, Joana; Sobkowiak, Michał J.; Sandberg, Johan K.; Leeansyah, Edwin
Abstract : A tool‐kit of adapted and optimized methods allowing for detailed functional examination of human MAIT cells responding to bacterial antigen. Abstract : Mucosa‐associated invariant T cells are a large and relatively recently described innate‐like antimicrobial T‐cell subset in humans. These cells recognize riboflavin metabolites from a range of microbes presented by evolutionarily conserved major histocompatibility complex, class I‐related molecules. Given the innate‐like characteristics of mucosa‐associated invariant T cells and the novel type of antigens they recognize, new methodology must be developed and existing methods refined to allow comprehensive studies of their role in human immune defense against microbial infection. In this study, we established protocols to examine a range of mucosa‐associated invariant T‐cell functions as they respond to antigen produced by Escherichia coli . These improved and dose‐ and time‐optimized experimental protocols allow detailed studies of MR1‐dependent mucosa‐associated invariant T‐cell responses to Escherichia coli pulsed antigen‐presenting cells, as assessed by expression of activation markers and cytokines, by proliferation, and by induction of apoptosis and death in major histocompatibility complex, class I‐related–expressing target cells. The novel and optimized protocols establish a framework of methods and open new possibilities to study mucosa‐associated invariant T‐cell immunobiology, using Escherichia coli as a model antigen. Furthermore, we propose that these robust experimental systems can also be adapted to study mucosa‐associated invariant T‐cell responses to other microbes and types of antigen‐presenting cells.